The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsphotonics.1c00628
|View full text |Cite
|
Sign up to set email alerts
|

MoTe2 PN Homojunction Constructed on a Silicon Photonic Crystal Cavity for High-Performance Photodetector

Abstract: We demonstrate a straightforward construction of MoTe2 PN homojunction on a silicon photonic crystal cavity, which promises the realizations of cavity-enhanced optoelectronic devices integrated on silicon photonic chips. The employed silicon photonic crystal cavity has an air-slot in the middle to split it into two parts, which directly function as two individual back-gate electrodes of the top-coated few-layer MoTe2. Beneficial from MoTe2’s ambipolar property, reconfigured (PN, NN, PP, NP) homojunctions are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…The photodetection performance of the device is comparable to other p-n homojunction photodiodes based on 2D semiconductors, such as WSe 2 and MoTe 2 . [17,18,22] In Figure S3 (Supporting Information), we present the short-circuit current I sc , open-circuit voltage V oc , power conversion efficiency γ, and fill factor FF of the InSe p-n diode as a function of incident laser power. The conversion efficiency of γ ≈ 2.3% and the fill factor of FF ≈ 0.38 are obtained, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The photodetection performance of the device is comparable to other p-n homojunction photodiodes based on 2D semiconductors, such as WSe 2 and MoTe 2 . [17,18,22] In Figure S3 (Supporting Information), we present the short-circuit current I sc , open-circuit voltage V oc , power conversion efficiency γ, and fill factor FF of the InSe p-n diode as a function of incident laser power. The conversion efficiency of γ ≈ 2.3% and the fill factor of FF ≈ 0.38 are obtained, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8–12 ] Gate‐tunable polarity has been implemented with a few 2D semiconductors such as black phosphorus and some transition metal dichalcogenides, [ 13–16 ] which enable reconfigurable field‐effect transistors (FETs) and p–n diodes with a simple dual‐gate structure that boost the development of digital technology and complementary electronics. [ 17–22 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Au electrodes with a thickness of 100 nm were then transferred on the ReS2 flake acting as the drain and source electrodes. [25][26][27][28][29] The heavily doped Si substrate could function as a bottom electrical gate. By applying an electrical voltage between the heavily doped Si substrate and the source electrode, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Recently, two-dimensional (2D) materials with layered structures have emerged as an attractive active medium for constructing optoelectronic devices. [6][7][8][9][10][11][12][13][14] It has been reported that versatile single-elementary and compound materials have layered stacking forms, which could be exfoliated into a 2D material with a thickness of few-atom layer. Therefore, plentiful electrical, optical, magnetic, and mechanical properties could be acquired from 2D materials.…”
Section: Introductionmentioning
confidence: 99%